Stakeholder Management And Compliance With Election Guidelines In Uganda: A Case Study Of The 2006 Elections In Kasese Town Council - Nadduli, Ahmed M.; Nabaho, Lazarus; Ochen-Chagara, Robert (Uganda Management Institute, 2009)
The study sought to examine the extent to which stakeholder management strategies employed by the E.C of Uganda, affect the compliance by election administrators with electoral guidelines. Specifically this research sought to examine the effect of stakeholder identification procedures on compliance with electoral guidelines in Kasese Town council, to establish the effect of stakeholder analysis on compliance with electoral guidelines in Kasese Town council, to examine the effect of the adopted strategy of training on compliance with electoral guidelines in Kasese Town council, to find out the effect of the adopted strategy of facilitation on compliance with electoral guidelines in Kasese Town council and to evaluate the moderating effect of political interference on compliance with electoral guidelines in Kasese Town council. The study focused on election administrators in Kasese Town Council, including polling officials, party agents, tally clerks and supervisors. Responses were sought from officials in the E.C planning departments and the media houses in Kasese District.
Keywords: management strategies; electoral guidelines; Kasese Town council